Feminism in a Female Teacher's Discourse in an EFL Classroom - Monica Patarroyo-Fonseca (Asociación Colombiana de Profesores de Ingles, 2021)
This research article on feminism gives an account of the interaction between a female teacher and her students at a public university in Tunja, Colombia. The study aims to evidence features of feminism within an English as a foreign language classroom by analyzing the transcriptions of the teacher's discourse using the Feminist Poststructuralist Discourse Analysis. As a result of the study, it can be stated that feminism is not determined by gender, but rather, it is an individual choice that is socially constructed and transmitted through power relationships. Findings suggest that being female or male does not guarantee having a definite position towards feminism; instead, it is mostly demarcated by the specific situations and circumstances that each individual experiences within a society.